Isolation and identification of the Myxobacterium Myxococcus fulvus from the Farms and study the inhibitory effect of cells and filtrates against pathogenic fungi (Baghdad Science Journal, 2018)
The study was performed to isolate and identify the Myxococcus fulvus from the one hundred samples of soils of farms. Special growth conditions had been used to support the growth of M.fulvus local isolates and suppressed the growth of other microorganisms like (Drying , High Temperature , High concentration of antibiotics and specific growth media ) M.fulvus isolates had been subjected to the morphological, cultural , biochemical examination for identification , as well as , study the inhibitory activites of cells and filtrates of localized isolates against some pathogenic fungi include (Trichophyton mentagrophytes , Microsporum gypseum , Aspergillus niger and Fusarium oxyporum ) by using three methods :- Cup assay , well diffusion and mixed culture , Results obtaind could be summarized as follows :- 1. (20) out of (100) soil samples , M.fulvus isolated as fruiting bodies depending on baiting technique by bacterial bait. 2. The media casiton – yeast extract agar was suitable for obtaind the best growth of vegetative swarms as pure culture .3. (8) local isolates were showed inhibitory effect against all of the tested pathogenic fungi .4. The concentrated filtrates of (3) local isolates were showed highly inhibitory effect than their unconcentrated filtrates against all of the tested pathogenic fungi .